Answer:
Step-by-step explanation:
-3x + 2y = 9
A. (3,9)
B. (-27,9)
C. (-3,-6)
D. (-9,9)
Answer:
(-9,-9)
Explanation:
The two given equations are:
3x - 4y = 9
-3x + 2y = 9
First step is to add the two equations in order to eliminate the x.
This will give us:
-4y + 2y = 9 + 9
-2y = 18
y = -9
Now, we substitute with the value of y in any of the equations to get x as follows:
3x - 4y = 9
3x - 4(-9) = 9
3x + 36 = 9
3x = -27
x = -9
Hope this helps :)
B. $612.00
C. $852.50
D. $803.00
Please explain the answer..
Answer:
z11= 523
z12= 714
z13= 468
Step-by-step explanation:
just did the assigment these are right
Answer:
first part is 1x3 and second part is
523
714
468
Step-by-step explanation:
just did it on edge
3x –y = 7
Substitution or Elimination
im using substitution
1. solve for variable for one of the equation
x + 3y = 9
x = 9 - 3y
2. Substitute the variable into one of the equation
3 (9-3y) - y = 7
27 - 9y - y = 7
27 - 10y = 7
-10y = 7 - 27
-10y = -20
y = 2
3. sub y = 2 into any equation to find x
3x - 2 = 7
3x = 7 -2
3x = 5
x = 5/3
X+3(2) = 9
x + 6 = 9
x = 9-6
x= 3
therefore there are two solutions x = 3 and x= 5/3